2013
DOI: 10.1371/journal.pgen.1003253
|View full text |Cite
|
Sign up to set email alerts
|

A Kinome-Wide RNAi Screen in Drosophila Glia Reveals That the RIO Kinases Mediate Cell Proliferation and Survival through TORC2-Akt Signaling in Glioblastoma

Abstract: Glioblastoma, the most common primary malignant brain tumor, is incurable with current therapies. Genetic and molecular analyses demonstrate that glioblastomas frequently display mutations that activate receptor tyrosine kinase (RTK) and Pi-3 kinase (PI3K) signaling pathways. In Drosophila melanogaster, activation of RTK and PI3K pathways in glial progenitor cells creates malignant neoplastic glial tumors that display many features of human glioblastoma. In both human and Drosophila, activation of the RTK and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
196
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(201 citation statements)
references
References 75 publications
(137 reference statements)
5
196
0
Order By: Relevance
“…Both Riok1 and Rps3a were both significantly altered by AMI in all three studied tissues. AMI treatment up-regulated Riok1 in all tissues studied, and pertinent to the remedial activities of AMI, it has been recently demonstrated that this kinase is a critical controller of AKTmediated cell survival (78). The consistent AMI-mediated reduction of Rps3a may also indicate that this is linked to potential cell protection mechanisms (79) and anti-inflammatory behavior (80).…”
Section: Discussionmentioning
confidence: 93%
“…Both Riok1 and Rps3a were both significantly altered by AMI in all three studied tissues. AMI treatment up-regulated Riok1 in all tissues studied, and pertinent to the remedial activities of AMI, it has been recently demonstrated that this kinase is a critical controller of AKTmediated cell survival (78). The consistent AMI-mediated reduction of Rps3a may also indicate that this is linked to potential cell protection mechanisms (79) and anti-inflammatory behavior (80).…”
Section: Discussionmentioning
confidence: 93%
“…NUAK2 is an AMPK-related kinase and a putative oncogene in melanoma (52,53). RIOK2 regulates glioblastoma growth and survival via regulating AKT (54). In this study, we focused on the more detailed characterization of CLK2, a dual specificity kinase implicated in the regulation of splicing due to its ability to phosphorylate SR proteins (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the affinity of RIOK2 for ERGi-USU is distinctively higher than all other kinases. RIOK2 is an atypical serine/threonine kinase required for the normal maturation of the 40S subunit of the eukaryotic ribosome in ribosomal biogenesis (39 ERGi-USU. These results showed that dose dependent decreases in RIOK2 protein levels in response to ERGi-USU closely mirrored the selective cell growth inhibitory effect of ERGi-USU (Fig 4B-E and inset).…”
Section: Ergi-usu Directly Binds and Inhibits Riok2 Proteinmentioning
confidence: 99%